THE EFFECT OF (Morinda citrifolia)WATER EXTRACT ON DRINKING WATER ON PHYSICAL QUALITY OF EGG IN LOHMANN BROWN LAYER HEN AGED 22-30 WEEKS - I P., Suarjana; Siti, N. W.; Bidura, I G. N. G. (Jurnal Peternakan Tropika, 2018)
This study aim to find out the effect of Morinda citrifolia extract on drinking water on physical quality of egg in Lohmann Brown layer hen aged 22-30 weeks. This study was conducted at chicken sheds own by farmers in Dajan Peken village, Tabanan Subdistrict, Tabanan District for three (3) months. Completely Randomized Design (CRD) was used with three treatments. Eack treatment was repeated 6 times using 36 Lohmann Brown chickens. Those chicken wos rised in 16 units battery type of shed. Treatments given were drink water without mengkudu water exstract as a control (A), treatment B was drink water units 2% mengkudu water extract and treatment C was drink water with 4% mengkudu water exstract. Variabels observed in this study were egg weight, white eggs percentage to egg weight, egg yolks percentage, and skin percentage. This study showed that egg weight of treatments B and C was significantly weigher (P<0,05) than control (A). White egg percentage of treatment B and C, on the another hand, was lighter compare to control (A). It was concluded that additional of ( Morinda citrifolia) water extract was abled to increase eggs weight, egg yolks percentage and skin percentage of the eggs, however reduce eggs white percentage age. Keywords : Morinda citrifolia, egg qulity, Lohmann Brown